Exploring and Developing Measurements for the Dimension of Contract Governance in Malaysia’s Public-Private Partnership Initiatives - Abdul Latif, Azlan Shah; Ali, Noor Azman; Ishan, Zahira; Jaharuddin, Nor Siah (Journal of Technology Management and Business, 2023)
Since 1983, Malaysia has been implementing public-private partnership (PPP) initiatives to acquire public infrastructure and services. These partnerships have been successful in improving public services and reducing public expenditure. Many researches have been conducted on the factors influencing the performance of PPP, including contract governance. However, due to the long duration and contractual obligations of PPP initiatives, there is still a lack of understanding about the influence of contract governance on the performance of these partnerships, highlighting a scarcity of study on contract governance in PPP contexts. Based on mono-method quantitative design, this study aims to develop a survey instrument to measure contract governance in PPP initiatives through Exploratory Factor Analysis (EFA). A pilot study has been conducted with 115 respondents and the data been analyzed using the Principal Component with the Rotation extraction technique. The results showed that all five components of contract governance in the study had a Cronbach's alpha greater than 0.70, indicating a high level of consistency and reliability. The results of this research provide significant knowledge on the measurement of contract governance on PPP project performance to the body of literature on partnership performance and contract governance, therefore assisting concessionaires and policymakers. Managers overseeing PPP projects should possess the ability to improve the performance of their projects by comprehending the impact of contract. governance on project performance.